Prazer-sofrimento de trabalhadores terceirizados da higiene e limpeza de um hospital público - Berni, Liana Bohrer (2013)
This is quantitative study, whose goal was to identify and measure the manifestations of pleasure-pain of outsourced workers of hygiene and cleanliness of a public hospital. Were used as data collection instruments, data collection of sociodemographic and labor indicators and scale of pleasure and pain at work (EIPST). Data were analyzed using SPSS software. The results indicate that the vast majority of these workers are women and in spare moments give priority to spend time with family, perform household chores, walking and traveling. Their main wishes for the future are to have a better job and health. Regarding measuring pleasure and suffering of these workers, it was found that the Professional Achievement and Recognition in this workplace are sources of pleasure and suffering that arises from the lack of Freedom of Expression and Emotional Exhaustion.